2017
DOI: 10.1016/j.tcr.2017.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Trans-colonic foreign body penetration of the retro-hepatic vena cava. Report of a case and review of the literature

Abstract: Foreign body ingestion is common in mentally impaired adults. Fortunately, the vast majority of all swallowed objects pass through the gastrointestinal tract uneventfully. For patients in whom conservative treatment fails, early endoscopic intervention is required. Surgery is seldom indicated and reports of perforation or penetration of the GI tract are anecdotal. We present a case of a 32 years old mentally impaired patient with a trans-colonic penetration of a foreign body into the retro-hepatic vena cava.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…[16] Gastrointestinal perforations due to foreign bodies occur along the GI tract due to acute bowel angles, the reduced caliber of the lumen and the transition from a a mobile tract of the bowel, like the ileum and sigmoid; to a fixed one such as cecum and rectum. [17] The analysis performed by Chung showed that the most common sites of perforation are the small bowel with 39.8% followed by duodenum (22%), colon (20.3%), rectum (10.6%) and sigmoid colon (5.5%) [7] [8]. Additionally, there are other less-represented areas of perforation such as the duodenojejunal flexure, the appendix, the colonic flexure, diverticula, and the anal sphincter.…”
Section: Discussionmentioning
confidence: 99%
“…[16] Gastrointestinal perforations due to foreign bodies occur along the GI tract due to acute bowel angles, the reduced caliber of the lumen and the transition from a a mobile tract of the bowel, like the ileum and sigmoid; to a fixed one such as cecum and rectum. [17] The analysis performed by Chung showed that the most common sites of perforation are the small bowel with 39.8% followed by duodenum (22%), colon (20.3%), rectum (10.6%) and sigmoid colon (5.5%) [7] [8]. Additionally, there are other less-represented areas of perforation such as the duodenojejunal flexure, the appendix, the colonic flexure, diverticula, and the anal sphincter.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported previously of a trans-colonic FB penetration to the retrohepatic vena cava in a mentally impaired patient. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…Patients will report a history of recurrent abdominal pain, fever of unknown origin, like our patient, nausea, obstipation, diarrhea etc. . The diagnostic work‐up usually consists of EGD, colonoscopy, computed tomography scan, and ultrasound, but failure to detect the toothpick was reported in 35% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…The patient's age, mental capabilities, clinical characteristics, and socioeconomic status should also raise questions. The surgeon should be prepared for life‐threatening situations such as major vascular involvement , as well as highly specialized and technically challenging procedures if the toothpick involves the hepatic hilum for instance .…”
Section: Discussionmentioning
confidence: 99%